Perekonomian pada Masa Khalifah Umar Bin Khattab: Kebijakan Ekonomi dalam Mengelola Baitul Mal - Aris, Muhammad; Mukhlis, Mukhlis; Permana, Febrian; Saputra, Randa Fajar; Alpizar, Alpizar; Herlinda, Herlinda (At-Tajdid : Journal of Islamic Studies, 2024)
The aim of writing this article is to find out and explain the economic policy during the time of Caliph Umar bin Khattab which can be used as a reference for alternative solutions to economic problems in Indonesia. The method used is library research by collecting data regarding the economic policies of Caliph Umar bin Khattab through data searches from the internet and print, in the form of articles and books. The results of the research are; the increase and rapid development of the people's economy during the time of Caliph Umar bin Khattab as it was, 1. Military Service Organisation. This organisation is responsible for distributing relief funds to people involved in warfare. The amount of the grant is determined by the number of family dependents of each recipient. 2. Judiciary and Executive Department. This department is responsible for paying the salaries of judges and executive officials. The amount of this salary is determined by two things: the amount of salary received must be sufficient to meet the needs of the family so as to avoid the practice of bribery and the amount of salary given must be the same and even if there is a difference, it is still within reasonable limits. 3. Islamic Education and Development Institution. This institution distributes financial assistance for propagators and developers of Islamic teachings and their families, such as teachers and preachers. 4. Social Security Institution. The aim of this department was that no one in the country should be deprived of the necessities of life. All those who were sick, aged, disabled, orphaned, widowed or for any other reason unable to earn their own living were given financial assistance on an annual basis from the Bait al-Mal.